Evaluasi Usability Pada Website E-commerce XYZ Dengan Menggunakan Metode Cognitive Walkthrough dan System Usability Scale (SUS) - Muhamad Arroofi Arga Kusumah; Retno Indah Rokhmawati; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
XYZ is an e-commerce that runs on various platforms, one of which is a website. XYZ provides a variety of features that support users to carry out the activities of buying and selling goods through the website. As time went on, XYZ became one of the most popular e-commerce sites. For this reason, we need to know the evaluation results of usability aspects and problems that exist on the XYZ website in order to maintain and improve the achievement of e-commerce XYZ. Usability aspects that are evaluated are learnability, effectiveness, efficiency and satisfaction. The method used in this study is cognitive walkthrough, usability testing and system usability scale (SUS). Evaluation using the cognitive walkthrough method and usability testing is carried out by five XYZ users who have never used e-commerce XYZ websites to find out existing problems and learnability aspects, effectiveness and efficiency. As for the usability scale (SUS) system, respondents numbered 20 people who had used e-commerce XYZ websites to find out aspects of satisfaction. After the evaluation was carried out, through the cognitive walkthrough method found 58 usability problems with 21 different problems. Then from usability testing obtained the learnability aspect value of 86%, effectiveness of 24% and efficiency of 0.02 seconds. While aspects of satisfaction using SUS obtained a value of 57,625. Recommendations for improving usability of e-commerce XYZ websites consist of two types of recommendations, namely, user interface design improvements and system improvements.